A Light‐Driven Microgel Rotor. Issue 46 (25th September 2019) - Zhang, Hang; Koens, Lyndon; Lauga, Eric; Mourran, Ahmed; Möller, Martin
Abstract: The current understanding of motility through body shape deformation of micro‐organisms and the knowledge of fluid flows at the microscale provides ample examples for mimicry and design of soft microrobots. In this work, a 2D spiral is presented that is capable of rotating by non‐reciprocal curling deformations. The body of the microswimmer is a ribbon consisting of a thermoresponsive hydrogel bilayer with embedded plasmonic gold nanorods. Such a system allows fast local photothermal heating and nonreciprocal bending deformation of the hydrogel bilayer under nonequilibrium conditions. It is shown that the spiral acts as a spring capable of large deformations thanks to its low stiffness, which is tunable by the swelling degree of the hydrogel and the temperature. Tethering the ribbon to a freely rotating microsphere enables rotational motion of the spiral by stroboscopic irradiation. The efficiency of the rotor is estimated using resistive force theory for Stokes flow. This research demonstrates microscopic locomotion by the shape change of a spiral and may find applications in the field of microfluidics, or soft microrobotics. Abstract : A spiral‐shaped microgel rotor is fabricated that operates in the low Reynolds number regime. The nonreciprocal deformations of the microgel are driven by light under nonequilibrium conditions and can be tuned by the modulation of light. The efficiency of the rotational motion is estimated using resistive force theory.